"Le Retour de la villégiature", III, 2 dans le triangle Strehler-Missiroli-Castri - Roberto Alonge (Il castello di Elsinore, 2020)
Starting from the second scene of the third act of Goldoni’s “Il ritorno dalla villeggiatura”, this paper deals with the perception that the most outstanding men of the Italian theatre – Giorgio Strehler, Mario Missiroli, Massimo Castri – had of Goldoni’s masterpiece in the last decades of the 20th century. We can identify three different modes of staging, which represent a starting point for a new scenic tradition in Goldoni.